2009
DOI: 10.1021/bi9007116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for the Denaturation of Proteins by Urea

Abstract: Understanding protein-solute interactions is one of the sizable challenges of protein chemistry; therefore, numerous experimental studies have attempted to explain the mechanism by which proteins unfold in aqueous urea solutions. On the basis of kinetic evidence at low urea concentrations, (1)H NMR spectroscopic analysis, and molecular orbital calculations, we propose a mechanistic model for the denaturation of RNase A in urea. Our results support a direct interaction between urea and protonated histidine as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 47 publications
2
50
0
1
Order By: Relevance
“…In the second step, denaturant and water molecules penetrate and solvate the hydrophobic core, resulting in global structural disruption. Experimental support for this model has, however, been scarce and indirect (4,6,13,26).Here, we demonstrate that the well-studied protein Escherichia coli ribonuclease HI (RNase H) (28-30) also rapidly populates a DMG state when exposed to denaturant and use this observation to explore the denaturant dependence of the DMG. We use multisite fluorescence resonance energy transfer (FRET) and kinetic thiol-labeling measurements to dissect the temporal order of protein expansion, side-chain disruption, and water solvation during GdmCl-induced unfolding.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In the second step, denaturant and water molecules penetrate and solvate the hydrophobic core, resulting in global structural disruption. Experimental support for this model has, however, been scarce and indirect (4,6,13,26).Here, we demonstrate that the well-studied protein Escherichia coli ribonuclease HI (RNase H) (28-30) also rapidly populates a DMG state when exposed to denaturant and use this observation to explore the denaturant dependence of the DMG. We use multisite fluorescence resonance energy transfer (FRET) and kinetic thiol-labeling measurements to dissect the temporal order of protein expansion, side-chain disruption, and water solvation during GdmCl-induced unfolding.…”
mentioning
confidence: 85%
“…D enaturants such as guanidinium chloride (GdmCl) and urea are classic perturbants used to probe the thermodynamics and kinetics of protein conformational changes, although their mechanism of action is poorly understood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In some of these studies, a dry molten globular (DMG) state has been observed on the native side of the free-energy barrier (16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the past year, a number of papers have appeared about whether a chaotrope destabilizes the native state or stabilizes the unfolded state (273)(274)(275)(276). In addition, urea appears to impede the hydrophobic collapse associated with formation of the globular native state (275).…”
Section: Chemical Denaturationmentioning
confidence: 99%
“…15,19,20 The issue of determination of the specific mode of urea action remains controversial, although the direct mechanism appears to be increasingly favored by the researchers. 17,21,22 The quest for understanding the relative importance of urea interactions with polar versus nonpolar groups is yet another recurrent theme in current investigations.…”
mentioning
confidence: 99%